1999
DOI: 10.1007/bf02349048
|View full text |Cite
|
Sign up to set email alerts
|

Transport mechanism of hydrogen through oxide film formed on zircaloy-4

Abstract: The diffusion behavior of hydrogen in the oxide films of zircaloy-4 specimens containing different size of Zr(Fe,Cr) 2 precipitates was examined. In the case of the specimen containing fine precipitates, hydrogen diffused uniformly through the zirconium oxide phase. The diffusion coefficient was 2-10 -25 m 2-s-~ at room temperature and 6-10 -19 m L s -z at 673 K. The transport rate of hydrogen in the oxide film of the specimen containing coarse precipitates was significantly higher than that of the specimen co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Especially, it has been reported that the intermetallic precipitates such as Zr(Fe, Cr) 2 play a role in the hydrogen pick-up process [35]. These second phase particles in a metallic state close to the metal/oxide interface would be cathodic sites for hydrogen according to Ramasubramanian et al [36] and "windows" or "bridges" for hydrogen to cross the metal/oxide interface [37].…”
Section: Discussionmentioning
confidence: 99%
“…Especially, it has been reported that the intermetallic precipitates such as Zr(Fe, Cr) 2 play a role in the hydrogen pick-up process [35]. These second phase particles in a metallic state close to the metal/oxide interface would be cathodic sites for hydrogen according to Ramasubramanian et al [36] and "windows" or "bridges" for hydrogen to cross the metal/oxide interface [37].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently the type of hydrogen species diffusing through the oxide vary depending on the process under study [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed Zircaloy-4 and M5 alloys contain mainly tin and niobium, respectively. Hydrogen diffusion coefficient in the oxide layer formed on M5 alloy is slightly higher than the one measured on Zircaloy-4 [13,14,16,17]. This difference is likely due to these alloying elements.…”
Section: Comparison With Previous Studiesmentioning
confidence: 65%
“…Anyway, research was initially focused on hydrogen diffusion through the oxide layer. In the past, the diffusion coefficient of hydrogen in the corrosion film was widely investigated either by 1) isotopic tracers, or 2) hydrogen implantation followed by Secondary Ion Mass Spectrometry (SIMS) or nuclear reaction analysis (NRA) [12] [13] [14] [15] [9] [16] [17] [18] [19] . However, due to the presence of two sub-layers in the oxide with different hydrogen transport properties [12], as well as the two types of hydrogen interaction within the oxide [9] or the polycrystalline structure of the oxide layer [19], apparent diffusion coefficient of hydrogen is difficult to evaluate accurately from measurements.…”
Section: Iintroductionmentioning
confidence: 99%